Development of mobile app: Funeral Services System (FSS) / Nur Aqilah Hanapi and Syafnidar Abdul Halim - Hanapi, Nur Aqilah; Abdul Halim, Syafnidar (Faculty of Computer and Mathematical Sciences, 2023)
The funeral services industry is an important sector that provides end-of-life care and support to families during a difficult and emotional time. However, this industry has traditionally been a challenging sector to navigate, with complex procedures and limited accessibility for families in need. The funeral planning and coordination process can be overwhelming, confusing, and time-consuming, adding additional stress to an already emotional time for families. The project is to develop a mobile app called Funeral Services System (FSS) to simplify the process of planning a funeral for the family members of the deceased. This project focuses on the development of a mobile app that enables users to access its features and functionalities through their devices. The app is being developed using the Flutter platform, and the code is being written using Visual Studio Code. This project will use Firebase as database. This project will utilize Firebase as the backend database infrastructure, leveraging its robust features and functionality for data storage, retrieval, and real-time synchronization. All the data entered by the user into the system will be stored in Firebase. In conclusion, the project has been executed successfully, resulting in the development of a functional and efficient system. The application's design, usability, and performance have met the outlined objectives, and effective functionality. We have run the testing to ensure the system functions as expected to achieve the objective. As a result of meticulous planning, systematic execution, and functionality testing, the project has achieved its intended goals. For the future work of development, we suggest integrating the payment future.